Counterfeiting in the Primary Industry Sector and the threat to New Zealand's economy - Ball R; Quirke S (Centre for Defence and Security Studies, Massey University)
Counterfeiting in its various iterations presents a potentially significant threat to our international reputation as a premium exporter of primary products. Taking existing international scholarly research in the area of food fraud, this article presents a typology of counterfeit activity as it pertains to the New Zealand primary industry sector. Through selected case studies, we explain how counterfeiting is a far more nuanced and complex problem than generally considered, and conclude that there should be a much stronger appetite for an integrated public-private identification framework that understands these variations in order to effectively pre-empt and mitigate the impact of primary product counterfeiting in this country.